"El Cartógrafo", A Map of the Dramatic Universe of Juan Mayorga - Martín Lago, Zoe (Talía. Revista de estudios teatrales, 2019)
Today, Juan Mayorga becomes again one of the great protagonists on the Madrid´s stage. His stablishment in the contemporary Spanish theatre stands one more time confirmed with the three own productions currently in tour –La lengua en pedazos, Reikiavik, El Cartógrafo–, and which he signs not just as dramatist but also as scene director. This communication proposes a commentary about El Cartógrafo, his last premiere, held by las Naves del Matadero of Madrid from January 26th to February 26th, 2017. “Definitio est negatio”. This key principle –repeated time and time again by the characters that inhabit El Cartógrafo– will be the leitmotiv guiding this analysis, whose objective is bringing to light the most relevant aspects of the political philosophy lying beneath the theatrical conception of the author. In this play, Mayorga emphasizes the important role of the borders to understand Europe, to get to understand the world and ourselves; A sadly current reflection in our political context. And in order to express the responsabily that the scenic creation must take over in our present day, he proposes in a poetic way, a comparison between the dramatist and the cartographer´s work. These premises taken, both text and staging of this play –which condenses as a monad all main characteristics in Mayorga´ s dramatic universe–, will be analyzed.